Saluran dan Margin Pemasaran Kopi Arabika di Kecamatan Timang Gajah Kabupaten Bener Meriah - Januar, Muhammad Alza; Khumaira, Khumaira; Fitri, Sri (Serambi Saintia : Jurnal Sains dan Aplikasi, 2024)
Coffee is a plantation commodity that dominates the global market, and Indonesia, with its high productivity, is one of the largest coffee producers. This research focuses on Timang Gajah District, Bener Meriah Regency, Aceh, which is an important arabica coffee production center. Even though Bener Meriah Regency has high coffee production, research on marketing channels and margins for Arabica coffee at the sub-district level is still limited. This research aims to explore the marketing channel structure and margins applied in the marketing of Arabica coffee in Timang Gajah District. This research method includes analysis of coffee production, marketing channel structure, and marketing margins implemented by farmers and marketing institutions in Timang Gajah District. The results show that the average income of Arabica coffee farmers in this sub-district reaches IDR 25,661,430, indicating a significant economic contribution. The first and second marketing channels in the research area are considered efficient, with efficiency levels of 9.20% and 7.02% respectively. The second marketing channel is proven to be the most efficient, indicating that the smaller the efficiency value of a marketing channel, the more efficient the channel.Keywords: Arabica Coffee, Marketing Channels, Marketing Margin